Bridging the gap between practice and research : forging partnerships with community-based drug and alcohol treatment - Lamb, Sara J.; Greenlick, Merwyn R.; McCarty, Dennis, Ph. D. (National Academy Press, 1998)
Prepared by real-life experiences in addiction treatment, including workshops and site visits, Bridging the Gap Between Practice and Research examines why research remains remote from treatment and makes specific recommendations to community providers, federal and state agencies, and other decision makers. The book outlines concrete strategies for building and disseminating knowledge about addiction; for linking research, policy development, and everyday treatment; and for helping drug treatment consumers become more informed advocates. In candid language, the committee discusses the policy barriers and the human attitudes - the stigma, suspicion, and scepticism - that often hinder progress in addiction treatment. The book identifies the obstacles to effective collaboration among the research, treatment, and policy sectors; evaluates models to address these barriers; and looks in detail at the issue from the perspective of the community-based provider and the researcher.
Keywords: Drug abuse -- Treatment -- Research -- United States.; Alcoholism -- Treatment -- Research -- United States.; Drug abuse -- Research -- United States.; Alcoholism -- Research -- United States.; National health services.; Health planning.; Health facilities.; Mental illness.; Diseases.; Research.; Medical care.; Science.; Physical sciences.; Alcoholism.; Academic medical centers.; Health Services; Health Planning; Health Facilities; Mental Disorders; Health Care Quality, Access, and Evaluation; Disease; Biomedical Research; Health Care Facilities, Manpower, and Services; Research; Delivery of Health Care; Health Care Economics and Organizations; Psychiatry and Psychology; Science; Natural Science Disciplines; Disciplines and Occupations; Substance-Related Disorders; Health Services Research; Alcohol-Related Disorders; Alcoholism; Community Health Services; Academic Medical Centers; Patient Care; Toxicomanie -- Traitement -- Recherche -- États-Unis.; Alcoolisme -- Traitement -- Recherche -- États-Unis.; Toxicomanie -- Recherche -- États-Unis.; Alcoolisme -- Recherche -- États-Unis.; Services de santé.; Santé publique -- Planification.; Équipements sanitaires.; Maladies mentales.; Maladies.; Recherche.; Prestation de soins.; Sciences.; Sciences physiques.; Toxicomanie.; Services de santé -- Recherche.; Troubles liés à l'alcool.; Alcoolisme.; Centres hospitaliers universitaires.; Soins médicaux.; health facilities.; mental disorders.; research (function); sciences (philosophy); physical sciences.; alcoholism.; science (modern discipline); SELF-HELP -- Substance Abuse & Addictions -- General.; PSYCHOLOGY -- Psychopathology -- Addiction.; Physical sciences; National health services; Mental illness; Medical care; Health planning; Health facilities; Diseases; Academic medical centers; Alcoholism -- Research; Alcoholism -- Treatment -- Research; Drug abuse -- Research; Drug abuse -- Treatment -- Research; United States